Illustrating the physics of core tungsten (W) transport in a long-pulse steady-state H-mode discharge on EAST. (1st June 2022) - Shi, Shengyu; Chen, Jiale; Jian, Xiang; Odstrčil, Tomáš; Clarrisse, Bourdelle; Wu, Muquan; Wu, Mingfu; Duan, Yanmin; Chao, Yan; Zhang, Ling; Cheng, Yunxin; Qian, Jinping; et al.
Abstract: The behavior of core tungsten (W) in a pure radio-frequency-heated long-pulse steady-state H-mode discharge in the Experimental Advanced Superconducting Tokamak (EAST) with an ITER-like divertor (ILD) is analyzed using experimental diagnostic data and modeled using a combination of drift-kinetic neoclassical and gyro-fluid turbulent software. In the steady state, the experimental core line-averaged W concentration ( C W ) is about 2 × 10 −5, which is evaluated using the intensity of the W unresolved transition array (W-UTA) spectral structure in the region of 45–70 Å (which is composed of W 27+ – W 45+ line emissions) through spectroscopy in the extreme ultraviolet region. W produces a peak of the radiated power density profile around a normalized radius of ρ ∼ 0.3. Therefore, W does not centrally accumulate in the experiment. A time slice of the steady-state is modeled, which accounts for both the neoclassical and turbulent transport components of W based on the self-consistent background plasma profiles simulated by TGYRO (Candy et al 2009 Phys. Plasmas 16 060704). It is found that turbulent transport dominates over neoclassical transport for W. In addition, the turbulent diffusion coefficient is large enough to offset the sum of the neoclassical and turbulent pinch (convection) velocities, so that the W density profile for a zero particle flux is not strongly peaked. By combining TGLF (Staebler et al 2017 Nucl. Fusion 57 066046) and NEO (Belli and Candy 2008 Plasma Phys. Control. Fusion 50 095010; 2012 Plasma Phys. Control. Fusion 54 015015) for the W transport coefficient with the impurity transport code STRAHL (Dux 2006 STRAHL User Manual ), the experimental C W and the information radiated by W can be reproduced closely. In addition, the effect of toroidal rotation on the W transport is also clarified.